Pengaruh Konseling Kelompok Cognitive Behavior Therapy Teknik Stress Inoculation Training Terhadap Stres Ulangan Siswa - Astrit Wironika; Padmi Dhyah Yulianti; Retnaningdyastuti Retnaningdyastuti (ILIN Institute Makassar, 2019)
This study aims to determine the effect of groups counseling cognitive behavior therapy approach with stress inoculation training techniques on tests stress experienced by students. This type of research is quantitative research with a true experimental design, research method with a pretest posttest control design. The sample in the study was 18 students of class VIII SMP N 4 Semarang who were taken using purposive sampling technique. The data collection tool used is stress scale. Based on the results of the calculation of the hypothesis test results obtained t count = 3.78. Then consulted with t table with a significance level of 5% which is 2.120 it shows that t count = 3.78 > t table = 2.120.